Political Communication Model in Indonesian Parliament - Arrianie, Lely (Universitas Muhammadiyah Yogyakarta, 2018)
The main objective of this study was to determine the model of political communication in the Indonesian parliament. The phenomenon of political communication using 'violence', occurred in Indonesian parliament period 1999-2004. This research was conducted with qualitative analysis, by developing interactionist theory, constructive, symbolic interaction in the political sphere. The results found that political communication in Indonesian parliament cannot be conceived as direct communication because the communication is interactional and transactional. Therefore, every political message is ultimately between interests and disagreements. It can build a conceptual model in which ‘violence’ in the delivery of political messages physically or psychologically occurs on the ‘front stage', 'middle stage’ and ‘backstage’.